An efficient one pot I2/DMSO mediated synthesis and molecular modeling of novel fused pyrimidine‐chromone hybrids bearing potential antibacterial and antifungal pharmacophores sites. (16th June 2021) - Pathan, Naziyanaz; Ali, Parvez; Rahatgaonkar, Anjali; Al‐Mousa, Khalid
Abstract: A series of novel ethyl‐l, 1, 2, 3, 6‐tetrahydro‐4‐methyl‐1‐(6‐methyl‐4‐oxo‐4H‐chromene‐2‐yl)‐2‐oxo/thioxo‐6‐phenyl pyrimidine‐5‐carboxylate compounds (2a–2k ) were synthesized using I2 /DMSO as a competent and cost‐effective catalyst in one pot green solvent system from corresponding chalcones (1a–1k ) in better yields. IR, 1 H‐NMR, 13 C‐NMR, Mass, and X‐ray diffraction spectroscopic techniques were used for the characterization of newly synthesized compounds. All the compounds were tested for in‐vitro antibacterial activities against gram‐positive and gram‐negative bacteria like Staphylococcus aureus, Salmonella abony, Staphylococcus epidermidis, and Escherichia coli . Antifungal activities were also performed against Candida albicans and Aspergilus niger . It was found that the presence of electron withdrawing group on the aromatic ring attached to chromone ring increases the antibacterial activities (2g, 2h, and 2k ); while the presence of electron releasing groups decreases activities. The presence of electron donating groups (─OCH3, ─Cl), on the phenyl ring attached to pyrimidine skeleton influenced negatively for the antibacterial activities. Abstract :